Complex and Simple Sentences: Issues Translation Correspondence in Russian and Chinese - Lihong An (Научный диалог)
The question of correspondences in the translation of complex sentences from Russian into Chinese is considered. It is noted that at present, translation correspondences in Russian and Chinese, including in the field of syntax, have not been studied enough. It is indicated that the difficulties of translation may be related to the discrepancy between the number of types of complex sentences in Russian, which are more than in Chinese. It is shown that some complex structures do not have an equivalent in Chinese and are translated into simple Chinese sentences. The author shows that complex sentences with explanatory clauses in Russian correspond not only to sentences with an included part in Chinese, but also to two-part and one-part sentences. The correspondence of complex sentences with attributive clauses, with relative clauses and degrees to different members of simple sentences of the Chinese language, as well as to chain sentences is substantiated. It is stated that some clauses of the tense (for example, with the conjunction NOT YET) correspond to circumstances, post-positional definitions of predicates, or one of the verbal constructions of a sentence with a sequential verbal predicate (连动句) in Chinese.